2015
DOI: 10.4269/ajtmh.14-0109
|View full text |Cite
|
Sign up to set email alerts
|

Primaquine Dosing Errors: The Human Cost of a Pharmaceutical Anachronism

Abstract: Abstract. Confusion between salt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Periods between primary infection and periods of clinical illness or relapse may be on the order of years and add to the clinical complexity of making the diagnosis [11]. Treatment is further complicated by uncertainty regarding the dosing of primaquine for P. ovale spp., with variation in practice based on regional experience and courses ranging from 7 to 14 days, weight-based recommendations ranging from 0.25 to 0.5 mg of base/kg/day, and dosing dependent on interpretation of base for salt components [22, 23]. Peruvian treatment experience and guidelines for P. vivax support a 7-day course of primaquine dosed at 0.5 mg base/kg/day [24].…”
Section: Discussionmentioning
confidence: 99%
“…Periods between primary infection and periods of clinical illness or relapse may be on the order of years and add to the clinical complexity of making the diagnosis [11]. Treatment is further complicated by uncertainty regarding the dosing of primaquine for P. ovale spp., with variation in practice based on regional experience and courses ranging from 7 to 14 days, weight-based recommendations ranging from 0.25 to 0.5 mg of base/kg/day, and dosing dependent on interpretation of base for salt components [22, 23]. Peruvian treatment experience and guidelines for P. vivax support a 7-day course of primaquine dosed at 0.5 mg base/kg/day [24].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of awareness may be due to limited community consultation and inadequate information dissemination processes in relation to the NHI. Studies in other developing countries have also shown a low level of awareness of health insurance especially among the informal sector of the population [ 1 , 13 ]. This study also suggests the need for more interventions to increase knowledge among NHI cardholders.…”
Section: Discussionmentioning
confidence: 99%
“…Further, those who access services often experience high out-of-pocket (OOP) expenses. High OPP expenses are a disincentive for people to access the care they need and can be catastrophic for poorer households [ 1 6 ]. Achieving UHC requires adequate and sustainable funding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation